2005
DOI: 10.1002/chin.200531199
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Magnesium Electrochemistry — A Challenge for Nanomaterials

Abstract: Inorganic chemistry Z 0100Advances in Magnesium Electrochemistry -A Challenge for Nanomaterials -[55 refs.]. -(AURBACH*, D.; GOFER, Y.; CHUSID, O.; LEVI, E.; LEVI, M. D.; VESTFRID, Y.; GIZBAR, H.; LANCRY, E.; Indian J. Chem., Sect. A: Inorg.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The electrolyte supported good cycling at the anode between the dissolved species and Mg metal as depicted in Figure , while Mg 2+ ion insertion and de‐insertion at two active sites in the channels of the Chevrel phase produced a discharge capacity of >50 mAh g −1 over 500 cycles; this will be further elucidated in cathode section. A series of studies on these organohaloaluminate/THF electrolytes investigated the active Mg species and the role of the Lewis acid R x AlCl 3‐x (x=0,1 and R is a small alkyl group) in supporting reversible Mg electrochemistry ,,. A transmetallation reaction occurs between the R 2 Mg base and R′ x AlCl 3‐x acid and electrochemically active species such as [MgCl] + or [Mg 2 Cl 3 ] + are generated during this transmetallation process (with the counter anions being [R n AlCl 4‐n ] − (n=1–4)).…”
Section: Rechargeable Mg Batteriesmentioning
confidence: 99%
“…The electrolyte supported good cycling at the anode between the dissolved species and Mg metal as depicted in Figure , while Mg 2+ ion insertion and de‐insertion at two active sites in the channels of the Chevrel phase produced a discharge capacity of >50 mAh g −1 over 500 cycles; this will be further elucidated in cathode section. A series of studies on these organohaloaluminate/THF electrolytes investigated the active Mg species and the role of the Lewis acid R x AlCl 3‐x (x=0,1 and R is a small alkyl group) in supporting reversible Mg electrochemistry ,,. A transmetallation reaction occurs between the R 2 Mg base and R′ x AlCl 3‐x acid and electrochemically active species such as [MgCl] + or [Mg 2 Cl 3 ] + are generated during this transmetallation process (with the counter anions being [R n AlCl 4‐n ] − (n=1–4)).…”
Section: Rechargeable Mg Batteriesmentioning
confidence: 99%
“…[2][3][4][5][6] Despite these attractive attributes of Mg batteries, there are still challenges pertaining to cathodes, electrolytes, anodes, and current collectors. 2,[7][8][9][10][11] In particular, electrolyte development is a crucial step in the research of magnesium battery systems since the electrolyte bridges the positive and negative electrodes, supports charge transfer in the circuit, and consequently needs to be compatible with both the cathode and anode materials for Mg batteries. 2 It remains a challenge to achieve a practical Mg battery electrolyte with good anodic stability, ionic conductivity, Mg deposition/dissolution efficiency, and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Among these alternative materials, magnesium-based batteries are promising candidates to replace Li batteries. [1][2][3][4][5][6][7][8][9] Mg as a battery anode offers several advantages over Li in terms of higher volumetric capacity (3833 mAh/cm 3 ), greater environmental friendliness, and safer use when exposed to air. 1,[10][11][12] Metallic Mg is also known to form compact and faceted films thus minimizing the risk of dendrite formation.…”
mentioning
confidence: 99%
“…From prior work, both the surface morphology and texture of electroposited Mg depend on current density. 6,10,22,28 Matsui showed that Mg deposited with electrolyte EtMgCl-2Me 2 AlCl in THF preferred a (001) texture for low current densities whereas high current densities favored a (100) orientation. 10 To further clarify the electrodeposition behavior of Mg, this work focuses on the effects of electrolyte chemistry on electrodeposited Mg.…”
mentioning
confidence: 99%